Ross-Ade : their Purdue stories, stadium, and legacies - Kriebel, Robert C., 1932- (Founders series., 2009)
Dave Ross (1871-1943) and George Ade (1866-1944) were trustees, distinguished alumni and benefactors of Purdue University. Their friendship began in 1922 and led to their giving land and money for the 1924 construction of Ross-Ade Stadium, now a 70,000 seat athletic landmark on the West Lafayette campus. Their life stories date to 1883 Purdue and involve their separate student experiences and eventual fame. Their lives crossed paths with U.S. First Lady Eleanor Roosevelt, Henry Ford, Amelia Earhart, and Will Rogers among others. Gifts or ideas from Ross or Ade led to creation of the Purdue Research Foundation, Purdue Airport, Ross Hills Park, and Ross Engineering Camp. They helped Purdue Theater, the Harlequin Club and more. Ade, renowned author and playwright, did butt heads with Purdue administrators at times long ago, but remains a revered figure. Ross's ingenious mechanical inventions of gears still steer millions of motorized vehicles, boats, tractors, even golf carts the world over.